Dehydrated vegetables : a survey of major markets (International Trade Centre UNCTAD/GATT GenevaCH, 1993)
Reviews the world market situation in dehydrated vegetables for Germany, Netherlands, U.K. and U.S.A. Gives comments and data on supply, demand, production, consumption, exports and imports; market characteristics and requirements; distribution channels; market access and import regulations; price information and customs duties.
DC